Characterization of mining fracture network development in overlying rock layers of deep mining in ordos basin - Wang, Xudong; Zhang, Suo; Pan, Ruanhang; Zhao, Yongqiang; Jia, Zhen; Tursinhali, Hainar; Ren, Xining; Kuerban, Alida (Frontiers in Earth Science, 2025)
With the gradual depletion of easily exploitable coal resources in the shallow crust, deep mining under complex geological conditions will become the new normal. Deep mining causes complex stress disturbances to the overlying strata. In order to study the deformation and fracture evolution characteristics of overburden under deep mining conditions, this paper studies the first mining face of a mine in Ordos, Asia, and combines a variety of research methods such as similarity simulation, fractal geometry and percolation theory to carry out research. First, the distribution morphology and development process of overburden mining cracks were studied through similarity simulation experiments, and the law of changes in the horizontal and vertical fracture density with the distance from the working face was obtained; secondly, the scale effect of the cracks was studied using fractal geometry theory, revealing the distribution law of cracks at different scales; finally, the development characteristics of the largest group of crack percolation were discussed, and the functional relationship between the percolation probability and the fractal dimension was given. The research results show that: the transverse and longitudinal fracture ratio of the overburden increases first, then decreases, and finally increases again as the working face advances. The mining cracks are generally distributed in an “M” shape with high ends and low middle; the change of fractal dimension is affected by factors such as the distribution, density, arrangement, connectivity and generation mechanism of the fracture network. The fractal dimension has two abrupt decrease points as the working face advances. According to the abrupt decrease points, the evolution of the fractal dimension can be divided into three stages; the percolation probability increases as the working face advances, and three growth rates appear in this process. According to the growth rate, the evolution of the percolation probability can be divided into three stages; the comparison of the changes in fractal dimension and percolation probability shows that the change nodes of the three stages are the same, and the fitting shows that the fractal dimension and the percolation probability have a good correlation. The research results can provide certain theoretical support for the zoning analysis and evaluation of mining damage in overburden strata under deep mining conditions.